STRATEGIES AND TECHNOLOGIES TO PREVENT HOSPITALACQUIRED INFECTIONS: LESSONS FROM SARS, EBOLA, AND MERS IN SAUDI ARABIA; A SYSTEMATIC REVIEW - Badr Bashir Al-Shammari, Eman Abdullah Aljumah, Salhah Bateal Alhazmy; Ali Salem Saleh Alyami, Mana Muhammad Haridan Alrubaie, Seham Abdulatif Alkhamis (Chelonian Research Foundation, 2022)
Background: In the context of preventing hospital-acquired infections (HAIs) during outbreaks such as SARS, Ebola, and MERS, robust infection control strategies and technological interventions play a pivotal role in ensuring the safety of healthcare workers and patients. Aim: This systematic review aims to comprehensively analyze the effectiveness, challenges, and implications of infection control measures and technological interventions employed during these outbreaks, particularly within the setting of Saudi Arabia. Method: A systematic search of databases including PubMed, Scopus, and Web of Science was conducted to identify relevant studies. Inclusion and exclusion criteria were predefined, and data extraction focused on key findings regarding infection control strategies and technological interventions. Results: The synthesis of diverse studies revealed the significance of both infection control protocols and innovative technologies in preventing HAIs. Challenges in adoption and terminology discrepancies were noted. Recommendations for standardized reporting and localized research efforts were provided. Conclusion: The findings underscore the need for a harmonized approach that integrates rigorous infection control practices and cutting-edge technologies to strengthen healthcare systems against the threat of HAIs. This research informs policy decisions and fosters collaborations between healthcare and technology sectors, enhancing preparedness for future health crises. Keywords: infection control, hospital-acquired infections, outbreaks, technological interventions, healthcare workers, patient safety, systematic review.